Propolis effectiveness on the reduction of blood glucose level and improvement of body weight in diabetic model's rat - Meida, Nur Shani; Purwanto, Bambang; Wasita, Brian; Indrakila, Senyum; Soetrisno, Soetrisno (Universitas Muhammadiyah Surabaya, 2024)
Propolis is an herbal medicinal plant that contains caffeic acid phenethyl ester. This natural polyphenol compound acts as an antioxidant and can reduce blood glucose levels and increase body weight. This study aims to determine the effectiveness of Gunung Lawu propolis in lowering blood glucose levels and increasing body weight in diabetic rats. The Wistar rats were induced with STZ 45 mg/kg BW and nicotinamide 110 mg/kg BW as diabetic model rats. Research subjects were taken randomly and divided into five groups: (1) Normal, (2) DM with no propolis, (3) DM 14 days + propolis 100 mg/kg BW/day (P1), (4) DM 14 days + Propolis 200 mg/kg BW/day (P2), and (5) DM 0 day + Propolis 200 mg/kg BW/day (P3). Propolis extract was given orally once a day for 14 consecutive days (in groups 3 and 4) and 28 consecutive days (in group 5). Blood glucose levels in the treatment group (P1, P2, and P3) decreased significantly (P1: 115.28 ± 4.7 mg/dL; P2: 98.36 ± 4.8 mg/dL; and P3: 87.36 ± 4, 2 mg/dL) compared with that in the DM group (272.07 ± 3.9 mg/dL). The body weight of the treatment group (P1, P2, and P3) increased significantly (P1: 180.60 ± 5.7 g; P2: 180.60 ± 4.2 g; and P3: 208.00 ± 5.1 gr) compared with that in the DM group (160.00 ± 3.2 gr). In conclusion, Propolis is effective in reducing blood glucose levels and improving (increasing) body weight in diabetic model rats.